2009
DOI: 10.1345/aph.1l641
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine-Induced Pain Syndrome in a Child Undergoing Hematopoietic Stem Cell Transplant

Abstract: Interventions aimed at reducing pain associated with CIPS may include the initiation of calcium-channel blocker therapy and conversion to an alternative calcineurin inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…The onset of CIPS is variable. It has been d as early as 3 days following the intravenous infusion of cyclosporine [7] and as late as 8 years, as seen in our patient. Similarly, association with the trough levels of the CIs is variable too.…”
supporting
confidence: 73%
“…The onset of CIPS is variable. It has been d as early as 3 days following the intravenous infusion of cyclosporine [7] and as late as 8 years, as seen in our patient. Similarly, association with the trough levels of the CIs is variable too.…”
supporting
confidence: 73%
“…CIPS is hypothesized to result from calcineurin-induced vascular changes that disturb bone perfusion and permeability, which leads to intraosseous vasoconstriction and BM edema [18,19]. This rare syndrome has been described in organ transplant recipients [32][33][34][35], where CIs must be maintained at a high concentration, whereas several cases of CIPS have been reported for patients undergoing HSCT [18,19,[36][37][38][39]. Moreover, in our study, 11 of 13 patients with HHV6-associated encephalitis/myelitis developed CIPS-like dysesthesia and/or pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…Jain and colleagues 18 reported that patients with hepatic dysfunction had a longer half-life of tacrolimus (corresponding to a lower clearance rate and higher trough plasma concentration); and the presence of CIPS is correlated to a high blood concentration of calcineurin inhibitors. 12,19 This may explain why the incidence of CIPS is high in our present study involving OLT patients; hence, specific attention should be paid to the application of tacrolimus in patients with liver dysfunction in clinical practice. In our study, the incidence of ONFH was only 1.7%, and the diagnosis was made about 1 year after transplant.…”
Section: Discussionmentioning
confidence: 83%